Nutrition literacy differs based on demographics among University students in Bengbu, China - Gao, Tianjing; Duan, Ying; Qi, Qi; Mo, Guangju; Han, Siyue; Liu, Huaqing; Zhang, Min (Frontiers in Public Health, 2023)
Background Nutrition literacy (NL) encompasses the knowledge and skills that inform individuals' food choices. This cross-sectional study explored factors associated with NL among Chinese university students in Bengbu, China. Methods A cross-sectional survey was carried out. Two thousand one hundred thirty-three university students were selected by stratified cluster sampling. A 43-item NL questionnaire was used to assess NL. Binary logistic regression was used to determine odds ratios (ORs) along with 95% confidence intervals (CIs) for NL and to test the interaction effects of multiple factors on total NL and its six dimensions. Results Of these participants, 1,399 (65.6%) were women and 734 (34.4%) were men. Students who were from urban areas (OR = 1.36, 95% CI: 1.08–1.72), were living with both parents (OR = 1.30, 95% CI: 1.02–1.65), and had high academic performance (OR = 1.85, 95% CI: 1.34–2.57) were more likely to report higher NL levels than did other students. The ORs for NL (OR = 1.60, 95% CI: 1.06–2.41), nutrition knowledge (OR = 1.51, 95% CI: 1.00–2.26), obtaining skills (OR = 1.76, 95% CI: 1.16–2.65), and critical skills (OR = 1.59, 95% CI: 1.05–2.39) were higher for medical students who had received nutrition education than for other students. The ORs for NL (OR = 2.42, 95% CI: 1.21–4.84), nutrition understanding (OR = 2.59, 95% CI: 1.28–5.25), and interactive skills (OR = 2.06, 95% CI: 1.04–4.08) were higher for only-child students and those with a monthly expenditure of >¥1500. Conclusions NL of university students differed in terms of place of origin, living arrangement, nutrition education, academic performance, and household income, and the findings imply that universities should have all students take a basic nutrition course to improve their NL.